Rapid assessment of avoidable blindness in Papua New Guinea: a nationwide survey. Issue 3 (23rd May 2018) - Lee, Ling; D'Esposito, Fabrizio; Garap, Jambi; Wabulembo, Geoffrey; Koim, Samuel Peter; Keys, Drew; Cama, Anaseini T; Limburg, Hans; Burnett, Anthea
Abstract : Objective: To estimate the prevalence and main causes of blindness and vision impairment in people aged 50 years and older in Papua New Guinea (PNG). Design: National cross-sectional population-based survey in National Capital District (NCD), Highlands, Coastal and Islands regions. Methods: Adults aged 50 years and above were recruited from 100 randomly selected clusters. Each participant underwent monocular presenting and pinhole visual acuity (VA) assessment and lens examination. Those with pinhole VA<6/12 in either eye had a dilated fundus examination to determine the primary cause of reduced vision. Those with obvious lens opacity were interviewed on barriers to cataract surgery. Results: A total of 4818 adults were examined. The age-adjusted and sex-adjusted prevalence of blindness (VA <3/60), severe vision impairment (SVI, VA <6/60 but ≥3/60), moderate vision impairment (MVI, VA <6/18 but ≥6/60) and early vision impairment (EVI, VA <6/12 but ≥6/18) was 5.6% (95% CI 4.9% to 6.3%), 2.9% (95% CI 2.5% to 3.4%), 10.9% (95% CI 9.9% to 11.9%) and 7.3% (95% CI 6.6% to 8.0%), respectively. The main cause of blindness, SVI and MVI was cataract, while uncorrected refractive error was the main cause of EVI. A significantly higher prevalence of blindness, SVI and MVI occurred in the Highlands compared with NCD. Across all regions, women had lower cataract surgical coverage and spectacle coverage than men. Conclusions: PNG has one of the highest reported prevalence of blindness globally. Cataract and uncorrected refractive error are the main causes, suggesting a need for increased accessible services with improved resources and advocacy for enhancing eye health literacy.